2007
DOI: 10.1177/104063870701900517
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in Vitro Susceptibility of Rodent Isolates of Pseudomonas Aeruginosa and Pasteurella Pneumotropica to Enrofloxacin

Abstract: Abstract. The objectives of this study were to determine and compare the in vitro enrofloxacin susceptibility of 94 Pseudomonas aeruginosa isolates obtained from enrofloxacin-treated and untreated mice and that of 40 Pasteurella pneumotropica strains and also to assess the efficacy and effects of enrofloxacin treatment of laboratory mice. The minimum inhibitory concentrations (MICs) of enrofloxacin against all the Ps. aeruginosa isolates were in the range of 1 to 4 mg/ml, whereas those against all the P. pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Treatment Antibiotic sensitivity testing in vitro indicated P. pneumotropica was significantly more sensitive than P. aeruginosa to enrofloxacin (Sasaki et al, 2007). Enrofloxacin in the drinking water at 85 mg/kg daily for 7 days eliminated clinical signs and infection in a closed breeding colonic of transgenic mice and after 14 days of treatment there were no detectable carriers when the colony was screened 4 weeks later (Matsumiya and Lavoie, 2003).…”
Section: F Pasteurella Pneumotropica Infectionmentioning
confidence: 99%
“…Treatment Antibiotic sensitivity testing in vitro indicated P. pneumotropica was significantly more sensitive than P. aeruginosa to enrofloxacin (Sasaki et al, 2007). Enrofloxacin in the drinking water at 85 mg/kg daily for 7 days eliminated clinical signs and infection in a closed breeding colonic of transgenic mice and after 14 days of treatment there were no detectable carriers when the colony was screened 4 weeks later (Matsumiya and Lavoie, 2003).…”
Section: F Pasteurella Pneumotropica Infectionmentioning
confidence: 99%
“…These results suggested that the treatment of the antibiotics was led to the reduced susceptibility of the isolate. In laboratory rodents, gentamicin and enrofloxacin have been generally used for the treatment of infectious diseases presumably caused by P. aeruginosa or another Gram-negative bacterium [10,25,26], while fluoroquinolones, carbapenems, and cephalosporins, such as ciprofloxacin, imipenem, and cefepime, may not be used for any bacterial infection in laboratory rodents in Japan and are strictly reserved for human use. In our study, no anamneses were found and none of antibiotics were administered in pet chinchillas.…”
Section: Discussionmentioning
confidence: 99%
“…For Salmonella strains, the MIC value varied between 0.06 and 0.25 µg/mL [ 60 , 61 ]. Significantly higher MIC values were obtained for Pseudomonas aeruginosa strains, ranging between 1 and 4 mg/mL [ 60 , 62 ].…”
Section: Efficacy Of Enrofloxacin In Veterinary Medicinementioning
confidence: 99%